Forecasting Output and Inflation: The Role of Asset Prices - Stock, James H; Watson, Mark W (Journal of Economic Literature, 2003)
This paper examines old and new evidence on the predictive performance of asset prices for inflation and real output growth. We first review the large literature on this topic, focusing on the past dozen years. We then undertake an empirical analysis of quarterly date on up to 38 candidate indicators (mainly asset prices) for seven OECD countries for a span of up to 41 years (1959 - 1999). The conclusions from the literature review and the empirical analysis are the same. Some asset prices predict either inflation or output growth in some countries in some periods. Which series predicts what, when and where is, however, itself difficult to predict: good forecasting performance by an indicator in one period seems to be unrelated to whether it is a useful predictor in a later period. Intriguingly, forecasts produced by combining these unstable individual forecasts appear to improve reliably upon univariate benchmarks.